Performance of Buddhist sunday school teachers and the effectiveness of Buddhist religious education Pesawaran and Pringsewu districts - Deni Prasetya; Dedi Kundana; Sandjaja Dharmatanna (International Journal of Science and Applied Science: Conference Series, 2025)
Teachers play a very strategic role as the front line in the learning process, so that optimal performance is a key factor in achieving educational goals. At Buddhist Sunday Schools in Pesawaran and Pringsewu Regencies, the learning process still faces problems, namely a monotonous, uninteresting, and boring learning atmosphere. This condition is influenced by the ineffective performance of some teachers, such as the use of learning methods that lack variety, ineffective interaction strategies with students, and minimal preparation of materials before teaching. This study aims to analyze the influence of Buddhist Sunday School teachers' performance on the effectiveness of Buddhist learning in the two districts. The research used a quantitative approach with a survey method. A total of 31 Buddhist Sunday School teachers were respondents. The research employed a questionnaire using a Likert scale to measure several indicators of teacher performance, including work discipline, organizational commitment and integrity, work motivation, work culture, educational leadership, teaching quality, and incentives. The findings revealed that work motivation emerged as the strongest aspect of teacher performance. Furthermore, data analysis indicated that teacher performance had a substantial impact on the effectiveness of Buddhist learning, although other factors also contributed. These results highlight that enhancing teacher performance is a crucial component in improving learning effectiveness. Such improvement should not only focus on instructional delivery but also emphasize strengthening teachers’ motivation, commitment, and mastery of teaching materials. In this way, better teacher performance will make a meaningful contribution to the learning development of Buddhist Sunday School students in Pesawaran and Pringsewu Regencies.